Analysis of International Cooperation in Exports at the Entikong Indonesia-Malaysia Border - Elyta Elyta; Herlan Herlan; Rupita Rupita; Azlyn Ahmad Zawawi; Syarif Redha Fachmi Al Qadrie (Citakonsultindo, 2024)
The Entikong border, as a trade gateway between Indonesia and Malaysia, is a crucial area to analyze regarding the impact of international cooperation in supporting export activities. This research aims to provide an in-depth understanding of the extent to which international cooperation has contributed to export development in the region. Involving a review of bilateral trade agreements, infrastructure development programs, and joint marketing initiatives, this analysis reflects the complex dynamics involving both countries. Infrastructure development cooperation, such as projects in the fields of transportation and border facilities, has had a significant impact on the efficiency of logistics and distribution of export products. Joint export promotion programs and the promotion of superior products are important instruments in diversifying export markets. This analysis evaluates the effectiveness of these initiatives in increasing product visibility in the global market. However, several challenges such as intense global competition and market dynamics need to be overcome to achieve more optimal market diversification. Through case studies, this research highlights the successes and challenges in implementing international cooperation. The results of this analysis provide a comprehensive picture of the impact of international cooperation in the context of exports at the Entikong Border. The policy implications found can be a guide for the government and stakeholders to increase the effectiveness of cooperation and strengthen the role of the Entikong Border as a dynamic trade center between Indonesia and Malaysia.